Studying Factors Affecting the One Stop Service Center: A Case Study in the Area of Maha Sarakham Province - Kejornrak, Arpakorn (Journal of Engineering and Industrial Technology, Kalasin University, 2023)
This research aims to examine the factors influencing the One Stop Service Center (OSSC) at the district level, using a case study in the Maha Sarakham Province area. The research methodology involves three steps: 1) Conducting preliminary data collection and interviews with individuals associated with factors affecting OSSC services across 13 centers in Maha Sarakham Province. 2) determining the weight ratios of factors obtained from the aforementioned survey. These ratios were presented to five provincial-level consumer protection experts with over five years of experience. The experts assessed each factor on a scale of 1–9 using the Expert Choice software, employing the Analytic Hierarchy Process (AHP) for multi-criteria decision-making analysis. 3) Establishing the weight ratios of each factor influencing the services provided by the OSSC. The research findings identified the most crucial five factors in the following sequence: C3: Convenience in accessing services via digital platforms (3E: e-service, e-learning, e-document) holds a factor weight of 0.606. C1: speed in service provision and access to up-to-date information with a factor weight of 0.191. C4: Empathy and professionalism of the staff, with a factor weight of 0.119. C5: Cleanliness and tidiness of the service facilities with a factor weight of 0.049. C2: Clarity and accuracy of the provided information have a factor weight of 0.036, respectively. And such factors are used as evaluation factors for each the OSSC to further develop the quality of services at the One Stop Service Center (OSSC).